2018
DOI: 10.3389/fnins.2018.00444
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Di-(2-ethylhexyl) Phthalate During Perinatal Period Gender-Specifically Impairs the Dendritic Growth of Pyramidal Neurons in Rat Offspring

Abstract: Di-(2-ethylhexyl) phthalate (DEHP), as a prevalent xenoestrogen endocrine disrupter, is omnipresent in the environment and commonly used in polyethylene plastic products. Although DEHP has potential adverse effects on multisystem organs, damage to the central nervous system is more significant. However, the consequences and mechanisms of DEHP exposure remain to be explored. The aim of this study was to investigate the effects and related mechanisms of maternal DEHP exposure on dendritic development of hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 83 publications
1
24
0
Order By: Relevance
“…People are inevitably exposed to phthalate through environmental contamination. Exposure to DEHP was associated with a variety of toxicological outcomes in mammals, reproductive toxicity, 39 neurotoxicity, 40 carcinogenicity, 41 hepatotoxicity, 42 and lipid metabolism disruption. 43 In this study, we focused on the harmful effect of this plasticizer on HEK-293 cell line, given that the kidney is one of DEHP target organ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People are inevitably exposed to phthalate through environmental contamination. Exposure to DEHP was associated with a variety of toxicological outcomes in mammals, reproductive toxicity, 39 neurotoxicity, 40 carcinogenicity, 41 hepatotoxicity, 42 and lipid metabolism disruption. 43 In this study, we focused on the harmful effect of this plasticizer on HEK-293 cell line, given that the kidney is one of DEHP target organ.…”
Section: Discussionmentioning
confidence: 99%
“…People are inevitably exposed to phthalate through environmental contamination. Exposure to DEHP was associated with a variety of toxicological outcomes in mammals, reproductive toxicity, neurotoxicity, carcinogenicity, hepatotoxicity, and lipid metabolism disruption …”
Section: Discussionmentioning
confidence: 99%
“…A common approach to assess the effects of perinatal exposure to phthalates is the maternal exposure model. In that sense, You et al (2018) investigated the effects of maternal DEHP exposure on dendritic development of hippocampal pyramidal neurons in a rat model. Wistar pregnant rats were intragastrically administered with DEHP from gestation day (GD) 0 to postnatal day (PND) 21; then, the offspring were sacrificed at PND 7, 14, and 21 to evaluate their dendritic length and complexity of dendritic arbors' pattern in pyramidal neurons of the hippocampus, as well as the expression of dendritic development‐related proteins (You et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been thought that women, especially pregnant women, are more susceptible to DEHP than men in the same living environment [12]. Moreover, it was deemed that DEHP and MEHP could pass through the placental barrier and the imperfect fetal cerebral blood barrier to affect fetal development [131415]. Studies have shown that maternal exposure to DEHP exerted deleterious effects on fetal immune, cardiovascular and endocrine system development [16171819].…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies on DEHP neurotoxicity have been conducted [1540414243444546], relatively little research has been done on its effect on the cerebellum, notably, toxicities and related mechanisms are still unclear. Therefore, the aim of the present study was to investigate the effects of DEHP on apoptosis in cerebellar granule cells (CGCs) and the underlying mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%